Rikki-tikki-tavi - Pinkney, Jerry; Kipling, Rudyard 1865-1936. (New York Morrow Junior Books, 1997)
A courageous mongoose thwarts the evil plans of Nag and Nagaina, two big black cobras who live in the garden.
113581
Keywords: Mongooses -- Juvenile fiction; Cobras -- Juvenile fiction; India -- Fiction; Picture books; Fiction; Juvenile literature